Nursing Intervention to Reduce Pediatric Pain in Needle Procedures in Emergency Department: A Systematic Review of Randomized Controlled Trial - Ode Irman; Anggia Riske Wijayanti; Yosefina Nelista (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Introduction: Needle procedures are common actions that are often encountered in emergencies. Emergency Departement (ED) with high workloads sometimes needle procedures are performed by force, thus causing uncontrolled pain, long-term negative psychological disorder, impairing physical evaluation and clinical outcome. The purpose of this review is to identify nursing intervention to reduce pediatric pain in needle procedures in ED. Methods: The literature search used the PubMed database with the keywords: nursing intervention, pain, needle procedures or injection and emergency department. Article criteria: 1) full text, 2) published in the 2016-2020 period, 3) employing Randomized Controlled Trial (RCT) research design, and 4) respondents aged 3-13 years old. Analysis of the quality of articles using the Critical Appraisal Skills Programme (CASP) and Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA). Result: 171 articles identified. Based on criteria and quality assessment of articles as many as 6 articles reviewed with focus intervention: virtual reality, parental presence, buzzy aplication, ditto aplication, humanoid robot and listening music. Conclusion: Nurses can use these interventions in the nursing care to reduce pediatric pain during needle procedures in ED.